Implications of Perhutani's CANOPY Brand Use for Nature Tourism After Trademark Registration Rejection by DGIP - Ratna Laniati; Dewi Sulistianingsih; Rini Fidiyani (Universitas Negeri Semarang, 2024)
Perum Perhutani has experienced an increase in tourism, necessitating standardization through the